2015
DOI: 10.1039/c5sm01071c
|View full text |Cite|
|
Sign up to set email alerts
|

Reply to the ‘Comment on “Cholesterol Solubility Limit in Lipid Membranes probed by Small Angle Neutron Scattering and MD simulations”’ by R. Epand, Soft Matter, 2015, 11, DOI: 10.1039/C4SM02819H

Abstract: In the comment by Epand et al. on our recent article, it is stated that the term “cholesterol solubility limit” is misused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…More recently, we found how defects in membrane packing induced by a supporting surface facilitate lipid flip-flop too and methodologies that can potentially have this effect on membranes result in inaccurate measured rates ( 39 ). From the MD side, we have also suggested that the tendency of the simulations to accumulate cholesterol in the bilayer center suggests that the energy barrier to flip is too low ( 46 , 47 ). Further, with TR-SANS, we have demonstrated that although exchange and flip-flop are coupled, it is their interdependence in the movement of lipids between and within membranes that allows for their distinction, even when the most significant contribution in TR-SANS comes from the exchange process as supported by the AIC test.…”
Section: Discussionmentioning
confidence: 94%
“…More recently, we found how defects in membrane packing induced by a supporting surface facilitate lipid flip-flop too and methodologies that can potentially have this effect on membranes result in inaccurate measured rates ( 39 ). From the MD side, we have also suggested that the tendency of the simulations to accumulate cholesterol in the bilayer center suggests that the energy barrier to flip is too low ( 46 , 47 ). Further, with TR-SANS, we have demonstrated that although exchange and flip-flop are coupled, it is their interdependence in the movement of lipids between and within membranes that allows for their distinction, even when the most significant contribution in TR-SANS comes from the exchange process as supported by the AIC test.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, while it is known that the pseudobilayer periodicity (34 Å) of cholesterol can only be readily detected by X-ray diffraction upon cholesterol phase separation in multi-lamellar vesicles, 3 the authors look for it in an X-ray diffraction pattern from a sample of unilamellar phospholipid/ cholesterol vesicles (ref. 1 and Fig. 1A).…”
mentioning
confidence: 79%
“…As authors of the ''Comment on 'Cholesterol solubility limit in lipid membranes probed by small angle neutron scattering and MD simulations''', we wish to comment on both the form and content of the Reply cited above. 1 In their original article, 2 Garg et al used neutron scattering techniques to determine the limiting amount of cholesterol which vesicles of either POPS or POPC can accommodate. They called this amount ''the cholesterol solubility limit''.…”
mentioning
confidence: 99%